The United States Foreign Policy towards Sub-Saharan Africa: Insights from Ghana, Tanzania, and Zambia, and the Omission of Nigeria - Ogunseye, Inioluwa Iyanu (Journal of Contemporary International Relations and Diplomacy, 2024)
In December 2022, the U.S.-Africa Leaders Summit was held in Washington DC, which had 49 heads of African states in attendance. As a follow-up, the United States Vice President, Kamala Harris, on March 27, 2023, was on state visits to Ghana, Tanzania, and Zambia. However, she did not stop in Nigeria. What does skipping Nigeria tell us about the U.S. foreign policy currently? This paper seeks to analyze Kamala Harris’s trips to Ghana, Tanzania, and Zambia as well as what the United States’ decision to skip Nigeria tells us about its current African foreign policy. The balance of power theory underpins this study. Secondary data sources were used. The study found out that Nigeria was excluded from the United States visit to Ghana, Tanzania, and Zambia due to insecurity and terrorism, questionable democracy, and human rights issues which are aligned to and constitute the US core national interests, economically, politically, and strategically. The state visit was aimed at restoring the U.S. damaged African relations. The study recommended that Nigeria must tackle the problems of bad governance and questionable democracy, terrorism, youth unemployment, and human rights issues for the development of stronger ties with the United States of America.